The inverted singlet–triplet gap: a vanishing myth? - Dreuw, Andreas; Hoffmann, Marvin (Frontiers in Chemistry, 2023)
Molecules with an inverted singlet-triplet gap (STG) between the first excited singlet and triplet state, for example heptazine, have recently been reported and gained substantial attention, since they violate the famous Hund's rule. Utilizing state of the art high-level ab initio methods, the singlet-triplet gap vanishes and approaches zero from below whatever is improved in the theoretical description of the molecules: basis set or level of electron correlation. Seemingly, the phenomenon of inverted singlet-triplet gaps tends to vanish the closer we look.